Analysis and Design for 3-RPRR Similarly Planar Fully Compliant Parallel Manipulator - Zhu Dachang; Li Yan; Zhang Tao (Jixie chuandong)
A fully compliant parallel manipulator can achieve multi-dimensional motions,but it has obvious limitations in the micro-position fields for the structure and size.A new mechanism which is called 3-RPRR similarly planar fully compliant parallel manipulator is designed.The design of such a new model is based on the configuration and geometric constraints of a 3-RPRR whole compliant manipulator.The model of3-RPRR fully compliant parallel manipulator and 3-RPRR similarly planar fully compliant parallel manipulator are designed firstly.Then,by utilizing the Hyperworks software,the finite element analysis of the two institutions and their chains are carried out,and combining with the principle of virtual work,the static stiffness models of the two mechanisms are deduced.At last,the modal frequency analysis is finished by the same software.The result shows that,the static stiffness,anti-interference performance and vibration resistance of 3-RPRR similarly planar fully compliant parallel manipulator are better than its prototype.